L’apocalypse dans les représentations de l’épidémie du VIH/sida : du religieux au médiatique - Lévy, Joseph (Frontières, 2013)
Since the 1980s, the epidemic of the HIV/AIDS, because of its acuteness, contributed to social representations and interpretations which include the theme of apocalypse. This paper will discuss this notion in three sets of discourses. Religious movements have reintroduced this idea in a fundamentalist way, but other theological schools criticize this use, proposing other interpretations. In philosophical texts, a more profane meaning is attached tot this concept, while retaining an hyperbolic dimension to signify the catastrophic dimensions of the epidemic, a perspective criticized par some intellectuals who produced counter-discourses more in conformity with an immanent vision of this infection. Medias repetitively use this notion to underscore the sensationalist dimension of the HIV/AIDS, in spite of pharmacological innovations which can erase this type of reference.
Free
Keywords: Apocalypse; HIV/AIDS; Medias; Philosophical texts; Religious movements; VIH/sida; mouvements religieux; médias; textes philosophiques